Rancangan Soal Geografi Menggunakan Taxonomy of Spatial Thinking Melalui Aplikasi Android - Syahrul Ridha; Mice Putri Afriyani; Anja Anja; Safroni Padang (Universitas Negeri Gorontalo, 2023)
Geography learning outcomes need to be measured with an effective instrument to determine the achievement of learning outcomes. This study aims to produce a geographic question model that is developed using a taxonomy of spatial thinking. The research procedure followed the ADDIE model, data were collected through expert validation of the question design and student responses. According to design experts, geography questions can be used to measure geographic knowledge, but a small improvement is needed on the component of spatial thinking, namely the using tools of representation in the form of maps or images with high resolution. The Android application that has been developed is SmartGeography. The geography questions in the SmartGeography application are valid, this can be seen from the score that is 86.63%. In addition, the SmartGeography Android application is effectively used in evaluating geography learning outcomes. This can be seen from the acquisition of a score of 87.83%. Thus, the SmartGeography application is good for people who have an interest in geography education.